Toward a Participatory Digital Ethnography of Blockchain Governance. (September 2022) - Rennie, Ellie; Zargham, Michael; Tan, Joshua; Miller, Luke; Abbott, Jonathan; Nabben, Kelsie; De Filippi, Primavera
Blockchain governance occurs through a combination of social and technical activities, involving smart contracts, deliberation within a group, and voting. These processes are significant as they demonstrate how governance of distributed infrastructures is evolving. While typologies of blockchain governance can be constructed by gathering on-chain interactions and formal rules, other aspects are more difficult to observe, including governance interactions occurring inside discussion forums. In this article, we discuss a participatory digital ethnography technique, whereby participants and researchers use a bespoke bot to identify governance interactions occurring within project forums (on Discord). The technique is designed to be used in conjunction with the analysis of software for the purpose of mapping and understanding the "governance surface" of different protocols. We describe our tools and methods for understanding automated futures through a case study of the SourceCred community, an organization using, developing, and maintaining open source software called SourceCred. The SourceCred codebase is also used by other decentralized communities for various organizational functions, including reputation and compensation.